POST-COVID-19 RESEARCH PRIORITIES: FROM LONG-TERM EFFECTS TO SOCIOECONOMIC RECOVERY - Ida Ayu Triastuti (Berkala Ilmiah Kedokteran Duta Wacana, 2024)
Some key areas of COVID-19 research should be continued, ultimately for the next 5 years, such as vaccine development and efficacy, long COVID-19, mental health impact, telemedicine and remote healthcare, epidemiological modeling and surveillance, socioeconomic impacts, and recovery strategies.